(untitled) - Schwartz, Stefanie (Ames, Iowa, 2005)
Psychoactive Herbs in Veterinary Behavior Medicine is an important guide for board-certified veterinary behaviorists, as well as veterinarians and veterinary students with a particular interest in behavior medicine. In addition, pet owners interested in alternative medicine for their misbehaving pets can use this well-rounded work to make informed decisions on the use of over-the-counter remedies
Keywords: Psychotropic plants,Veterinary diet therapy,Chế độ điều trị thú y,Alternative veterinary medicine; Therapeutic use